KEMAMPUAN MENGKONSTRUKSI BUKTI MATEMATIS MELALUI REALISTIC MATHEMATICS EDUCATION DI SUMATERA UTARA - Mariadi; Dedy Juliandri Panjaitan; Cut Latifah Zahari (LPPI UMN AL WASHLIYAH, 2025)
The ability to construct mathematical proofs is a crucial higher-order thinking skill in mathematics learning; however, it remains a major challenge for many students. These difficulties are reflected in students’ limited ability to develop logical arguments and systematically connect definitions, theorems, and mathematical facts. This study aims to analyze students’ ability to construct mathematical proofs through the implementation of the Realistic Mathematics Education (RME) approach in North Sumatra. This research employed a descriptive qualitative approach with purposively selected secondary-level students as research subjects. Data were collected through tests of mathematical proof construction ability, observations of the learning process, and in-depth interviews. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results indicate that the implementation of RME helps students understand mathematical concepts contextually, develop logical reasoning, and improve their ability to construct mathematical proofs in a gradual and structured manner. Students were able to relate contextual problems to formal mathematical concepts, formulate arguments based on clear reasoning, and draw logical conclusions. Therefore, the RME approach contributes positively to the development of students’ mathematical proof construction abilities. This study recommends the use of RME as an alternative instructional approach to enhance the quality of mathematics learning, particularly in developing students’ mathematical proof abilities.